Histological study of the interaction between Exserohilum Longirostratum, barnyard grass, and rice var. Mr219 - Mohammad Hailmi, Sajili (2012)
The course of infection and the development of Exserohilum longirostratum (Subramanian) Sivanesan on barnyardgrass (Echinochloa crus-galli (L.) Beauv. spp. crusgalli) and rice (Oryza sativa L. var. MR219) were studied under light microscopy (LM) and scanning electron microscopy (SEM). Observation under SEM indicated similarity of the gross anatomy of both rice and barnyard grass leaves. Meanwhile, germination of the conidium of E. longirostratun was found to be not influenced by inoculation time as the conidia started to germinate 4 hours after the inoculation on both leaf surfaces. However, the patterns and number of germ tubes and appressoria formation were influenced by host plants. On barnyard grass, the orimary infection process consisted of the conidial germination. elongation of the germ tube. formation of the aooresorial initials. maturation of